Functional nanostructured ionic liquid-based block copolymer systems for energy applications - May, Alyssa Winter, author; Bailey, Travis S., advisor; Reynolds, Melissa, committee member; Sambur, Justin, committee member; Lear, Kevin, committee member (Colorado State University. Libraries, 2021)
Room-temperature ionic liquids (RTILs) are pure molten salts that have zero vapor pressure, a wide range of thermal stability, negligible flammability, and high ionic conductivity. These qualities make them desirable as electrolyte replacements for the more common lithium salt-doped carbonate solvents which are ubiquitous in current battery technology despite being exceptionally flammable. Use of liquid electrolytes, even non-flammable ones, has its drawbacks and challenges, like preventing leakage of the electrolyte and maintaining good contact with electrode surfaces, particularly when the battery electrodes or container become physically warped. With the emergence of flexible electronics technologies like foldable phones, bendable displays, and "wearables," interest has grown in developing solid electrolytes that are mechanically robust and sufficiently good ionic conductors, as they greatly expand the design possibilities for batteries. Block copolymers (BCPs) are an ideal platform from which to develop solid electrolyte materials as the variety of polymerizable blocks and physical properties that can be derived from them are nearly limitless. In this dissertation, we explore two methods for incorporating ionic liquid components into solid BCP materials, and thoroughly delve into their interesting chemical, physical, and mechanical properties to demonstrate their potential as functional materials. The first method is the direct, sequential polymerization of both ionic liquid-based and traditional monomers to create poly(ionic liquid) (PIL) BCPs that can microphase separate to form ordered nanostructures. We report on the synthesis of both cobalt-containing and imidazolium-based PIL BCPs and provide a comprehensive examination of their melt-state phase behavior, including the observation of all four equilibrium morphologies available to diblock copolymers: lamellae (Lam), bicontinuous gyroid (Gyr), hexagonally packed cylinders (Hex), and spheres (S). From the morphological phase behavior, we were able to build two phase diagrams and extract critical information about the materials, such as block density of the methyl-imidazolium PIL block. This is an essential parameter for BCP design that enables researchers to target specific morphologies when creating similar materials in the future. The morphology of solid-state conductive materials like PIL BCPs has direct implications on their transport properties, as only certain morphologies (Gyr, S) can have fully continuous domains in which ions can flow, so fully understanding the spectrum of phase behavior in a BCP material is incredibly important for creating truly functional materials from them. The second method is the integration of RTIL into amphiphilic, non-ionic BCPs as a selective swelling solvent to create ion gels, or gel polymer electrolytes (GPEs). We have designed these BCPs, based on melt-state phase separating blends of polystyrene-b-poly(ethylene oxide) (SO) and polystyrene-b-poly(ethylene oxide)-polystyrene (SOS) in which the hydrophilic O block is the majority component, to form hydrophobic spherical domains of S that form a tethered, physically crosslinked networked that acts like an elastic solid when swollen. We demonstrate that SOS BCPs swollen in the RTIL 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, or [EMIM][TFSI], have exceptional ionic conductivity, elasticity, distensibility, recovery rates, bulk toughness, and fracture toughness. This rare combination of multiple excellent mechanical properties and high ionic conductivity makes SOS GPEs auspicious candidates as solid electrolytes in energy transport and storage applications.
Keywords: hydrogels; polymer mechanics; soft material mechanics; ion gels; block copolymers; polymer physics